Tinjauan Hukum Perjanjian Baku Pada PT AXA Mandiri Financial Services - Safitri, Rahmad (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The implementation of the standard agreement in the Insurance Agreement according to Law No. 40 of 2014 confirms that insurance is an agreement made between the insurer and the insured, which is regulated in Article 246 of the KUHD. As an agreement that affirms the fulfillment of binding rights and obligations between the insured party and the insurer, both parties must comply with all points of agreement that are part of the agreement in the agreement. This article is classified as a literature research with a qualitative approach. The methodology used is the study of descriptive analysis. The results of the study concluded that, according to the applicable legality, if an uncertain event occurs, AXA Mandiri makes a change to the policyholder for losses suffered based on the results of fund management.